WAR AND INTERNATIONAL OBLIGATIONS: INVESTIGATING RUSSIAN FEDERATION'S COUNCIL OF EUROPE MEMBERSHIP CESSATION PROCEDURE AS A SANCTION FOR ARMED AGGRESSION AGAINST UKRAINE - Nazarko, Artem (Collection of scientific papers «ΛΌГOΣ», 2023)
Following the end of World War II, there was a rise in the creation of international intergovernmental organizations, which achieved significant success at the regional level. In 1949, in response to calls for unity, ten states signed the Statute of the Council of Europe, which invited all European countries that acknowledge and safeguard fundamental human rights and freedoms, uphold the principles of the rule of law, and actively collaborate to attain the Statute's goal (Article 3) to become members [1]. The Council of Europe has been instrumental in protecting human rights and freedoms in European member states and the continent as a whole. Its legal mechanism for safeguarding human rights is recognized as one of the best. However, concerns have been raised about whether member states of the Council of Europe fully adhere to their international legal obligations and if being a member state ensures complete compliance with human rights standards. Presently, almost all European countries, including Russian Federation until recently, are members of the Council of Europe.